2021
DOI: 10.1111/jocs.15623
|View full text |Cite
|
Sign up to set email alerts
|

A case of a pregnant patient with COVID‐19 infection treated with emergency c‐section and extracorporeal membrane oxygenation

Abstract: Coronavirus disease 2019 (COVID‐19) causes the development of severe acute respiratory distress syndrome. Pregnant women may be at increased risk for the development of severe disease. We present the case of a pregnant patient who developed respiratory failure due to COVID‐19 and rapidly decompensated requiring intubation. Despite mechanical ventilation, the patient's respiratory status continued to worsen. At bedside, cardiothoracic surgeons, obstetricians, intensivists, and neonatologists discussed balancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In a series by Barrantes et al, 8 nine COVID-19 positive patients required ECMO support and required cesarean sections either before or after ECMO cannulation. Rushakoff et al 1 also reported a case of a 30-yearold COVID-19 positive pregnant patient with a 29-week fetus taken first to emergency C-section followed by immediate v-v ECMO support. Additionally, in a report by Hou et al, 2 a third trimester COVID-19 positive patient had her pregnancy terminated followed by ECMO support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a series by Barrantes et al, 8 nine COVID-19 positive patients required ECMO support and required cesarean sections either before or after ECMO cannulation. Rushakoff et al 1 also reported a case of a 30-yearold COVID-19 positive pregnant patient with a 29-week fetus taken first to emergency C-section followed by immediate v-v ECMO support. Additionally, in a report by Hou et al, 2 a third trimester COVID-19 positive patient had her pregnancy terminated followed by ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although pregnancy in itself does not increase the likelihood of acquiring COVID-19, the physiological changes associated with pregnancy may render pregnant women susceptible to severe respiratory distress and severe disease. 1,2 Here we present a case of a COVID-19 positive 36-year-old 26-week pregnant patient with respiratory failure requiring ECMO support and C-section while on ECMO. COVID-19 has presented many difficult decision-making scenarios for physicians.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most reports are of individual cases or small case series, as a result of a limited number of patients and difficulty in conducting a randomized trial on peripartum ECMO support, specifically in COVID-19-infected pregnant patients. For example, an article by Rushakoff et al showed an identical situation, where the MDT involved in the management of their patient preferred to deliver her before ECMO deployment [ 11 ], while in another report, the patient continued her pregnancy and delivered after resolution of her acute illness [ 12 ].…”
Section: Discussionmentioning
confidence: 99%